Distribution Channel for Local Farm-based Produce: A study On Small Farmers During Pandemic Crisis - Noor Fzlinda Fabeil; Juliana Langgat; Khairul Hanim Pazim; Roslinah Mahmud (Universiti Malaysia Sabah, 2022)
It has been contended in many studies that small enterprises are more sensitive to crisis. Small enterprises tend to progress relatively slower than larger enterprises during a crisis, and in fact may fail to sustain the business within three years after a crisis strike. The pandemic crisis in Malaysia has disrupted several important sectors especially agricultural due to the disruption of transportation and retails services. Small farmers experience dumping of farm produces due to the restricted delivery channels and loss of regular market. Small farmers are believed to demonstrate a viable strategy for the sustainability of their businesses during a crisis, through the use of an alternative distribution approach to deliver their perishable goods to consumers. Through structured interviews with two small farmers in Ranau, Sabah, this paper presents their perspectives on the alternative distribution strategy they had undertaken during a crisis. The results of the study provide insights into how the hub distribution approach might assist small farmers in managing the impact of the crisis on their business and can therefore be used as an effective distribution approach in the future.